Development, Validation, and Reliability of a Sedation Scale in Horses (EquiSed) - Oliveira, Alice Rodrigues de; Gozalo-Marcilla, Miguel; Ringer, Simone Katja; Schauvliege, Stijn; Fonseca, Mariana Werneck; Trindade, Pedro Henrique Esteves; Puoli Filho, José Nicolau Prospero; Luna, Stelio Pacca Loureiro (Frontiers in Veterinary Science, 2021)
The lack of standardization of sedation scales in horses limits the reproducibility between different studies. This prospective, randomized, blinded, horizontal and controlled trial aimed to validate a scale for sedation in horses (EquiSed). Seven horses were treated with intravenous detomidine in low/high doses alone (DL 2.5 μg/kg + 6.25 μg/kg/h; DH 5 μg/kg +12.5 μg/kg/h) or associated with methadone (DLM and DHM, 0.2 mg/kg + 0.05 mg/kg/h) and with low (ACPL 0.02 mg/kg) or high (ACPH 0.09 mg/kg) doses of acepromazine alone. Horses were filmed at i) baseline ii) peak, iii) intermediate and iv) end of sedation immediately before auditory, visual and pressure stimuli were applied and postural instability evaluated for another study. Videos were randomized and blindly evaluated by four evaluators in two phases with one-month interval. Intra- and interobserver reliability of the sum of EquiSed (Intraclass correlation coefficient) ranged between 0.84–0.94 and 0.45–0.88, respectively. The criterion validity was endorsed by the high Spearman correlation between the EquiSed and visual analogue (0.77), numerical rating (0.76), and simple descriptive scales (0.70), and average correlation with head height above the ground (HHAG) (-0.52). The Friedman test confirmed the EquiSed responsiveness over time. The principal component analysis showed that all items of the scale had a load factor ≥ 0.50. The item-total Spearman correlation for all items ranged from 0.3 to 0.5, and the internal consistency was good (Cronbach's α=0.73). The area under the curve of EquiSed HHAG as a predictive diagnostic measure was 0.88. The sensitivity of the EquiSed calculated according to the cut-off point (score 7 of the sum of the EquiSed) determined by the receiver operating characteristic curve, was 96% and specificity was 83%. EquiSed has good intra- and interobserver reliabilities and is valid to evaluate tranquilization and sedation in horses.